Correlation between mindfulness and death anxiety among the elderly: Hubungan antara mindfulness dengan kecemasan terhadap kematian pada lanjut usia - Nazira; Rahma Yurliani; Elvi Andriani Yusuf; Dina Nazriani (Talenta Publisher, 2020)
This study examines the relationship between mindfulness and death anxiety among elderly people. The study was conducted at a nursing home involving 150 elderly people. The results showed that mindful elderly people were less likely to experience death anxiety. We discussed the importance of mindfulness to enhance the quality of life of aging people. Penelitian ini mengkaji hubungan antara mindfulness dan kecemasan menghadapi kematian pada lansia. Penelitian dilakukan di sebuah panti jompo yang melibatkan 150 lansia. Hasilnya menunjukkan bahwa lansia yang mindful cenderung tidak cemas menghadapi kematian. Kami membahas pentingnya mindfulness untuk meningkatkan kualitas hidup lansia.